Obtain the partial differential equation by eliminating the arbitrary constant from the relation
x^2/a^2 +y^2/b^2 +u^2/c^2 =1
"\\frac{x^2}{a^2} + \\frac{y^2}{b^2} + \\frac{u^2}{c^2} = 1"
Differentiating w.r.t. x
"\\frac{2x}{a^2} + \\frac{2u}{c^2}\\frac{du}{dx} = 0 \\;\\;\\;(1)"
Again differentiating (1) w.r.t. x
"\\frac{2}{a^2} + \\frac{2ux}{c^2} \\frac{d^2u}{dx^2} + \\frac{2}{c^2} (\\frac{du}{dx})^2 = 0"
Multiplying by x
"\\frac{2x}{c} + \\frac{2ux}{c^2} \\frac{d^2u}{dx^2} + \\frac{2}{c^2} (\\frac{du}{dx})^2x = 0"
From (1):
"\\frac{2x}{a^2} = \\frac{-2u}{c^2} \\frac{du}{dx} \\\\\n\n\\frac{-2u}{c^2} \\frac{du}{dx} + \\frac{2ux}{c^2} \\frac{d^2u}{dx^2} + \\frac{2x}{c^2} (\\frac{du}{dx})^2 = 0"
Put
"\\frac{du}{dx} = p \\\\\n\n\\frac{d^2u}{dx^2} = s \\\\\n\n-up + uxs + xp^2 =0"
Comments
Leave a comment